Lactobacillus species signature in association with term and preterm births from low-income group of Pakistan. (3rd August 2022) - Aslam, Sohail; Sayeed Saraf, Viqar; Saleem, Sidra; Saeed, Salma; Javed, Sundus; Junjua, Maira; Bokhari, Habib
Abstract: Aim/Purpose of study: It is estimated that around 15 million babies are born prematurely every year and approximately one million children die each year due to complications of preterm birth (PTB). Many survivors face a lifetime of disability, including learning disabilities and visual and hearing problems. The current study aimed to characterize Lactobacillus species isolated from vaginal swabs and determine their antibiotic susceptibility. Material and methods: 40 term and 20 preterm samples were processed by culturing on MRS agar and initial identification was carried out using sugar fermentation reactions and 16S rRNA PCR. Moreover, Lactobacillus species from preterm and term cases using paired samples, i.e. vaginal swabs and placenta tissues from 8 preterm delivering mothers were further recruited for metagenomics study to possibly detect uncultured Lactobacillus species known to cause PTB. Results: 40% samples from preterm delivering mothers lack any Lactobacillus species whereas in contrast vaginal microflora of all term delivering mothers carry one or more species of Lactobacillus. L. crispatus (46% in term group and 25% preterm group) was found to be the most abundant group followed by L. jensenii (25% in both groups) and L. gasseri (19% in term group and 10% in preterm group). The antimicrobial susceptibility profile suggests that preterm isolates were least resistant to linezolid (20% resistance rate) and trimethoprim/sulfamethoxazole (22% resistant rate) compared to term isolates (>60% for each drug group). Furthermore, the metagenomics data for paired samples (8 VS and 8 PT) from extreme PTB suggested that Lactobacillus Iners was the main difference between term and preterm deliveries. Moreover, overall lack of lactobacillus species or presence of rogue Lactobacillus species such as L. iners and L. vaginilis is associated with PTB. ERIC-PCR analysis using Lactobacillus crispatus revealed that all the pre-term samples are closely related and fall in same cluster while all the term samples fall in different cluster. Conclusion: The study not only provides a baseline data of distinct signatures of associated lactobacillus species with the PTB which may be further transmitted to new born infants but also developing further therapeutic interventions to better manage the PTB.